Fur mites of the genus Schizocarpus Trouessart (Acari: Chirodiscidae) from the Eurasian beaver Castor fiber tuvinicus Lavrov (Rodentia: Castoridae) in the Azas River (Tuva Republic, Russia) - Bochkov, Andre V.; Saveljev, Alexander P. (Zootaxa, 2012)
Sixteen species of the genus Schizocarpus Trouessart, 1896 (Acari: Chirodiscidae) are recorded from six live individualsof the Eurasian beaver Castor fiber tuvinicus Lavrov (Rodentia: Castoridae) captured at the Azas River (Tuva, Russia).Six species are described as new: Schizocarpus azasicus sp. nov., S. daberti sp. nov., S. heideckei sp. nov., S. lavrovi sp.nov., S. unzhakovi sp. nov., and S. tuvinicus sp. nov. Ten previously described species are as follows: S. brachyurus(Dubinina, 1964), S. grandis (Dubinina, 1964), S. fedjushini (Dubinina, 1964), S. gozdziewskii Bochkov et al., 2012, S.insignis Fain and Lukoschus, 1985, S. modestus Fain and Lukoschus, 1985, S. pusillus Fain and Lukoschus, 1985, S.radiatus Fain and Lukoschus, 1985, S. subornatus Fain and Lukoschus, 1985, and S. zurowskii Bochkov et al., 2012.Schizocarpus intercalatus Fain and Lukoschus, 1985 syn. nov. and S. parabrachyurus Fain and Lukoschus, 1985 syn. nov.are considered as junior synonyms of S. brachyurus; S. ventricosus Fain and Lukoschus, 1985 syn. nov. is considered as a junior synonym of S. latus (Dubinina, 1964).